2004
DOI: 10.1096/fj.04-1683fje
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal abnormalities and increased malignancy of skin tumors in human epidermal keratin 8‐expressing transgenic mice

Abstract: Keratins K8 and K18 are the major components of the intermediate filament cytoskeleton of simple epithelia. Increased levels of these keratins have been associated with invasive growth and progression to malignancy in different types of human and murine epithelial tumors (including skin tumors), and even in tumors from nonepithelial origin. However, it has not yet clarified whether K8/K18 expression in tumors is cause or consequence of malignancy. Given the increasing incidence of epidermal cancer in humans (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 46 publications
9
45
1
Order By: Relevance
“…By contrast, in accordance with their poorly differentiated phenotype, C57-CYLD C/S SCCs showed scarce expression of K1 and K10, limited to isolated cells (Figure 5a and data not shown). On the contrary, keratin K8, a marker of malignancy in skin tumors (Casanova et al, 2004) showed extensive staining in the C57-CYLD C/S carcinomas and weak expression in the C57-Control tumors (Figure 5a). K13, a keratin characteristic of internal stratified squamous epithelia, which is aberrantly expressed in skin tumors and is also considered a marker of tumor progression (Winter et al, 1990;Moreno-Maldonado et al, 2008) was also highly expressed in the C57-CYLD C/S tumors and it was hardly detected in the C57-Control SCCs (Figure 5a).…”
Section: The Expression Of Cyld C/s In Tumoral Epidermal Cells Increamentioning
confidence: 99%
“…By contrast, in accordance with their poorly differentiated phenotype, C57-CYLD C/S SCCs showed scarce expression of K1 and K10, limited to isolated cells (Figure 5a and data not shown). On the contrary, keratin K8, a marker of malignancy in skin tumors (Casanova et al, 2004) showed extensive staining in the C57-CYLD C/S carcinomas and weak expression in the C57-Control tumors (Figure 5a). K13, a keratin characteristic of internal stratified squamous epithelia, which is aberrantly expressed in skin tumors and is also considered a marker of tumor progression (Winter et al, 1990;Moreno-Maldonado et al, 2008) was also highly expressed in the C57-CYLD C/S tumors and it was hardly detected in the C57-Control SCCs (Figure 5a).…”
Section: The Expression Of Cyld C/s In Tumoral Epidermal Cells Increamentioning
confidence: 99%
“…For example, H-ras and v-src upregulate VEGF expression in fibroblasts and epithelial cells (Rak et al, 1995a, b;Arbiser et al, 1997;Jiang et al, 1997;White et al, 1997;Charvat et al, 1999;Casanova et al, 2002). Similarly, upregulation of insulin-like growth factor 1 (Lahm et al, 1996;Valentinis et al, 1997;Werner et al, 2000) and plateled-derived growth factor B (Sonobe et al, 1991) is induced by a wide range of oncogenes.…”
Section: Proangiogenic Factorsmentioning
confidence: 99%
“…We have used the PB keratinocyte cell line for these purposes. These cells were obtained from a chemically induced mouse skin papilloma, but they do not show increased EGFR expression nor mutations in Ha-ras gene (Yuspa et al, 1986;Casanova et al, 2002). Moreover, when PB keratinocytes are used in xenograft experiments, they are poorly tumorigenic: few tumors are generated, and those obtained display very long latency, reduced growth rate and highly differentiated phenotypes (Yuspa et al, 1986;Casanova et al, 2002;Segrelles et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These cells were obtained from a chemically induced mouse skin papilloma, but they do not show increased EGFR expression nor mutations in Ha-ras gene (Yuspa et al, 1986;Casanova et al, 2002). Moreover, when PB keratinocytes are used in xenograft experiments, they are poorly tumorigenic: few tumors are generated, and those obtained display very long latency, reduced growth rate and highly differentiated phenotypes (Yuspa et al, 1986;Casanova et al, 2002;Segrelles et al, 2002). On the other hand, increased expression of Akt, and thus increased activity, promoted a dramatic enhancement in tumorigenic behavior, with reduced latency, increased growth rate and less differentiated phenotypes (Supplementary Figure 1, see also Segrelles et al, 2002Segrelles et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%